Experimental investigation of single wood particle combustion in air and different O2/CO2/H2O atmospheres. (15th May 2023) - Mack, A.; Maier, J.; Scheffknecht, G.
Highlights: Single wood particle combustion experiments in a horizontal pipe oven at 900 °C. Three different particle sizes (4 mm, 6 mm and 8 mm) investigated. Experiments in air, air/H2 O, O2 /CO2, O2 /CO2 /H2 O and O2 /H2 O atmospheres. Reduced combustion times in oxyfuel compared to air at the same O2 concentration. Lower temperatures and longer combustion times in wet atmospheres with 40 vol-% of steam. Abstract: This work aims to obtain experimental data of the combustion behavior of single wood particles under oxyfuel conditions relevant for grate incineration facilities. The objectives are to derive insights on how the application of the oxyfuel technology affects the conditions in the fuel bed in grate firing systems and to generate an experimental data basis for simulation activities. Therefore, combustion experiments of single spherical particles with 4 mm, 6 mm and 8 mm diameter have been performed with varying O2 concentrations (10–50 vol-%) in O2 /CO2, O2 /CO2 /H2 O and O2 /H2 O atmospheres at 900 °C. The duration of the characteristic stages of the thermal conversion process, volatile and char combustion, has been investigated by means of recording videos with distinct frame rate. Additionally, the temperature of the flame as well as the particle has been measured throughout the combustion process. It has been found that the total combustion times of the particles under oxyfuel conditions at 21 vol-% oxygen in dry and wet atmospheres are generally shorter compared to the respective air cases throughout all particle sizes. Increasing the oxygen concentration further reduces the combustion durations. At the same oxygen concentration, the temperature of the volatile flame is increased during oxyfuel combustion compared to air conditions. Comparable particle temperatures during char combustion under air conditions have been measured at 30 vol-% oxygen under oxyfuel conditions. In general, both temperatures increased with rising oxygen concentration and the smallest particles did show the highest values. However, the smallest particles were more strongly affected by the changes in the atmosphere causing higher differences in the measured temperatures. Addition of 40 vol-% steam had a decreasing effect on the temperatures with higher extent at the bigger particle sizes. However, increasing the steam concentration to 70 vol-% at the same oxygen concentration caused higher temperatures.